Impact of antithrombotic therapy on acute and delayed intracranial haemorrhage and evaluation of the need of short-term hospitalisation based on CT findings after mild traumatic brain injury: experience from an oral and maxillofacial surgery unit: original article - Sakkas, Andreas; Weiß, Christel; Wilde, Frank; Ebeling, Marcel; Thiele, Oliver Christian; Mischkowski, Robert Andreas; Pietzka, Sebastian (European journal of trauma and emergency surgery, 2023)
The primary aim was to compare the prevalence of acute and delayed intracranial haemorrhage (ICH) following mild traumatic brain injury (mTBI) in patients on antithrombotic medication referred to a clinic for oral and plastic maxillofacial surgery. The secondary aim was to evaluate the need for short-term hospitalisation based on initial radiological and clinical findings.